Determinan Yang Mempengaruhi Hasil Error Pada Metode Pemeriksaan Tes Cepat Molekuler Tuberkulosis - Aturut Yansen (Jurnal Medika Hutama, 2022)
ABSTRACT Background, methods, result, discussion, conclussion in times new roman 11 Molukuler Rapid Test is one of the laboratory examinations to diagnose tuberculosis. In the problematic process the presence of MYCOBACTERIUM tuberculosis DNA cannot be found and there is a system failure so that the interpretation issued is an error. Based on data obtained at citeureup health center in 2019, the total error rate was 5% but there was the highest error reaching 13%. So that researchers aim to find out the determinants that affect the high number of errors in molecular rapid test examinations. The method used in this study is the observation method with total sampling, analyzed with crosstab test and multiple linear regression test using SPSS version 16.0. Based on the results of the f and R2 tests known to sig.0.004 < 0.05 and the value of Fcount 4,004 > Ftable 3.04 means that there is an influence of sample quality factors, sample processing procedure factors, cartridge quality factors and officer competency factors simultaneously on error results and these factors affect error results by 44.9% the remaining 55.1% influenced by other variables not studied in this study and Based on the t test, it is known that the partial influence that causes high error results is a sample quality factor based on sig. 0.002 < 0.05 and the tcount value -3,117 >ttable -2,834.